2023
DOI: 10.1093/nar/gkac1236
|View full text |Cite
|
Sign up to set email alerts
|

ONECUT2 regulates RANKL-dependent enterocyte and microfold cell differentiation in the small intestine; a multi-omics study

Abstract: Microfold (M) cells reside in the intestinal epithelium of Peyer's patches (PP). Their unique ability to take up and transport antigens from the intestinal lumen to the underlying lymphoid tissue is key in the regulation of the gut-associated immune response. Here, we applied a multi-omics approach to investigate the molecular mechanisms that drive M cell differentiation in mouse small intestinal organoids. We generated a comprehensive profile of chromatin accessibility changes and transcription factor dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 100 publications
1
3
0
Order By: Relevance
“…Secretory cells in the epithelial compartment of the small intestine consisted of PCs, goblet cells, tuft cells, and enteroendocrine cells in both IE-HuR −/− and littermate mice, whereas absorptive cells were marked by various enterocytes (Fig 2A). Notably, PCs were marked by high expression of Defe5 and Rg3a mRNAs, whereas ISCs were marked by transcripts including Ascl2, Lgr5, Olfm4, Rgmb, and Smoc2 mRNAs, as reported previously (Elmentaite et al, 2021;Luna Velez et al, 2023). Cell cluster analysis revealed that the numbers of PCs and ISCs decreased in IE-HuR −/− mice compared with control littermate mice, which were consistent with the findings obtained from studies using immunostaining assays as shown in Fig 1.…”
Section: Altered Cell Type-specific Gene Expression Profiles In the H...supporting
confidence: 91%
“…Secretory cells in the epithelial compartment of the small intestine consisted of PCs, goblet cells, tuft cells, and enteroendocrine cells in both IE-HuR −/− and littermate mice, whereas absorptive cells were marked by various enterocytes (Fig 2A). Notably, PCs were marked by high expression of Defe5 and Rg3a mRNAs, whereas ISCs were marked by transcripts including Ascl2, Lgr5, Olfm4, Rgmb, and Smoc2 mRNAs, as reported previously (Elmentaite et al, 2021;Luna Velez et al, 2023). Cell cluster analysis revealed that the numbers of PCs and ISCs decreased in IE-HuR −/− mice compared with control littermate mice, which were consistent with the findings obtained from studies using immunostaining assays as shown in Fig 1.…”
Section: Altered Cell Type-specific Gene Expression Profiles In the H...supporting
confidence: 91%
“…For example, CUX1 affects both myeloid and lymphoid differentiation, and CUX2 controls HOX gene expression during forelimb development [ 41 , 42 ]. ONECUT1 and ONECUT2 regulate early retinal cell fates, while the latter also regulates intestinal cell differentiation [ 43 , 44 ]. SATB1 supports self-renewal of HSCs inhibiting their differentiation and orchestrates erythroid development via regulation of globin genes [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…BMP-signaling inhibits ONECUT2 in trigeminal sensory neuron differentiation [ 54 ], demonstrating that this pathway plays a physiological role in ONECUT2 regulation in some cell types. We failed to detect any regulatory impact for TNFRSF11A (also named RANK); although, this receptor has been shown to activate ONECUT2 in enterocytes of the small intestine [ 43 ]. In T-cells, ONECUT2 is regulated by TBX21/T-bet [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they might be used to define how different microorganisms or patient‐specific microorganisms, even the whole microbiota of gut, regulate intestinal physiological processes and pathological progression (Figure 5B). The close‐knit integration with gene editing 233,234 and multiomics, 235,236 which will provide important insights into the mechanisms underlying microbial–host interactions, is also being expected (Figure 5C). These technologies will enable comprehensive and detailed detection of the modification or expression levels of various components, from DNA to RNA to protein, so as to clarify the functional changes after the interaction between intestinal cells and bacteria.…”
Section: Conclusion and Prospectsmentioning
confidence: 94%